Single electron-hole pair generation using dark-bright solitons conversion control - Punthawanunt, S.; Jomtarak, R.; Teeka, C.; Yupapin, P. P.; Ali, J. (My University, 2011)
In this paper, we present the new concept of single electron-hole pair generation by using dark-bright solitons conversion control based on microring resonator coupled to one arm MZI. By using some suitable parameters and found that the single electron-hole pair are seen, therefore, the single electron-hole pair generate can be storage and controll within the design system.
Keywords: dark-bright solitons conversion control; single electron-hole pair generation